ANALYSIS OF THE LEVEL OF FINANCIAL SECURITY OF COMMERCIAL BANKS - Мартинюк, Олексій (Modern engineering and innovative technologies, 2023)
In the article, the author reveals the content and features that affect the financial security of a commercial bank. Based on the SWOT analysis, the author identifies the strengths and weaknesses in ensuring the financial security of commercial banks, a